Changing Students Minds and Achievement in Mathematics: The Impact of a Free Online Student Course - Boaler, Jo; Dieckmann, Jack A.; Pérez-Núñez, Graciela; Sun, Kathy Liu; Williams, Cathy (Frontiers in Education, 2018)
This study reports on the impact of a “massive, open, online course” (MOOC) designed to change students' ideas about mathematics and their own potential and improve their mathematics achievement. Many students hold damaging fixed mindsets, believing that their intelligence is unchangeable. When students shift to a growth mindset (believing that their intelligence is malleable), their achievement increases. This study of a MOOC intervention differs from previous mindset research in three ways (1) the intervention was delivered through a free online course with the advantage of being scalable nationwide (2) the intervention infused mindset messages into mathematics, specifically targeting students' beliefs about mathematics (3) the research was conducted with a teacher randomized controlled design to estimate its effects. Results show that the treatment group who took the MOOC reported more positive beliefs about math, engaged more deeply in math in class, and achieved at significantly higher levels on standardized mathematics assessments.